Analysis of Researching Dynamics and Structure of Consumer Expenditure of the Russian Population - Buneeva, Raisa Ilyinichna; Buneeva, Maria Vitalyevna; Toropov, Valery Valeryevich; Khryuchkina, Elena Alekxeevna (International Journal of Economics and Financial Issues, 2016)
The model of consumption, consumer behavior (character of consumption), volume and structure of consumption are determined by the person's style and lifestyle. In their turn, style and lifestyle are formed on the basis of the consumer's level of life, i.e., the level of prosperity and benefits consumption defined by the needs, ways and forms to satisfy them based on the real consumer demand. The article shows the results of the analysis related to the researches that prove the influence of the consumer factor on the level of people's lives by dynamics and structure of consumer expenditures. Keywords: Level of people's life, consumer factor, resources' provision of consumption, households, economic entities, consumption factor. JEL Classifications: D01, D14, I31, J31